Buku pintar raja-raja Jawa : dari Kalingga hingga Kasultanan Yogyakarta : mengungkap sejarah dan biografi para raja berdasar fakta terbaru - Adji, Krisna Bayu, 1980- (Yogyakarta : Araska Publisher, 2012)
History and biography of kings in Java, Indonesia.
Includes bibliographical references (p. 203-209).
Keywords: Java (Indonesia) -- Kings and rulers; Java (Indonesia) -- Kings and rulers -- Biography; Java (Indonesia) -- History